2019
DOI: 10.9734/jerr/2019/v4i316904
|View full text |Cite
|
Sign up to set email alerts
|

Sanding and Shaping Characteristics of Gmelina arborea Grown in Two Ecological Zones in Ghana

Abstract: Poor machining of wood generates more residues which leads to low recovery in wood processing. Therefore, the availability of appropriate wood machining techniques would promote efficient utilization of logs. This study looked at the shaping and sanding properties of Gmelina arborea - a lesser-known species in Ghana - in order to promote its efficient utilization. Six trees from plantations at the Wet Evergreen and Dry Semi-Deciduous Forest Zones were extracted and processed into lumber using LT 15 horizontal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…is a plantation-grown species in Ghana introduced from Southeast Asia and promises to be a good alternative to the dwindling primary timber species. It is regarded as a medium-density lesser-used species (LUS) (Mitchual et al 2018, Mitchual et al 2019. Minkah et al (2021a) reported that thermal modification of gamhar (Gmelina arborea Roxb.)…”
Section: Introductionmentioning
confidence: 99%
“…is a plantation-grown species in Ghana introduced from Southeast Asia and promises to be a good alternative to the dwindling primary timber species. It is regarded as a medium-density lesser-used species (LUS) (Mitchual et al 2018, Mitchual et al 2019. Minkah et al (2021a) reported that thermal modification of gamhar (Gmelina arborea Roxb.)…”
Section: Introductionmentioning
confidence: 99%